Molecular Surgical Pathology - Cheng, Liang; Eble, John N.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Molecular Surgical Pathology provides a concise review of recent advancement of molecular pathology in each organ system. The text is intended as a “first knowledge base” in the rapidly evolving field of molecular pathology and is organized in a user friendly outline format. Each chapter is organ-based and covers important aspects of molecular pathology and its impact on our daily practice of surgical pathology. The topics presented herein constitute the fundamentals and core base of knowledge required for the daily practice of surgical pathology. This book focuses on the practical utilities of molecular techniques and molecular biomarkers in daily practice of surgical pathology. The emphasis is on the impact of molecular pathology for tumor classification, diagnosis and differential diagnosis as well as its implications for patient management and personalized care. Numerous tables, diagrams and color illustrations are included throughout.  Molecular Surgical Pathology will prove a very useful resource for pathologists in training who are preparing for the Board and in-service examination.  It will also be a unique and invaluable resource for medical oncologists, physicians, other medical professionals and basic research scientists with interest in molecular pathology of human cancers.
Molecular Pathology of Colorectal Cancer -- Molecular Pathology of Pancreatic  Cancer -- Molecular Pathology of Liver Tumors -- Molecular Pathology of Gallbladder Cancer -- Molecular Pathology of Lung Cancers -- Molecular Pathology of Breast Cancer -- Molecular Pathology of Ovarian Cancer -- Molecular Pathology of Endometrial Cancer -- Molecular Pathology of Kidney Tumors -- Molecular Pathology of Prostate Cancer -- Molecular Pathology of Urinary Bladder Cancer -- Molecular Pathology of Testicular Cancer -- Molecular Pathology of Cutaneous Melanoma and Nonmelanoma Skin Cancer -- Molecular Pathology of Head and Neck Cancer -- Molecular Pathology of Soft Tissue and Bone Tumors -- Molecular Pathology of the Central Nervous System -- Molecular Pathology of Endocrine Cancers.
Keywords: Pathology; Oncology .; Laboratory medicine; Cancer research; Pathology; Oncology; Laboratory Medicine; Cancer Research